Exploring Cash Waqf Models for Financial Modernisation in Dayah-Based Islamic Higher Education Institutions in Aceh: A Sociology of Islam Perspective - Abdullah, Amiruddin; Razali, Ruslan (JURNAL INDO-ISLAMIKA, 2024)
Throughout Islamic education, waqf has been integral to the ummah, especially in education. The potential for developing funding for educational institutions from new waqf sources, particularly cash waqf, is significant. This study examines the opportunities for implementing cash waqf models in Islamic Higher Educational Institutions (PTKI) in Aceh, focusing on modernizing the financial system at dayah-based PTKIS. This research employs a mixed-method approach to identify a gap in the effective implementation and management of cash waqf, including qualitative interviews and quantitative data analysis. The study explores current practices, challenges, and potential solutions in asset management, fundraising, investment strategies, and the utilization of waqf proceeds. Findings show substantial opportunities for innovation and improvement in these areas despite obstacles such as awareness and administrative issues. Based on the sociology of Islam perspective, this research highlights the interaction between local and universal aspects of Islam, emphasizing the importance of humanistic values in modern financial practices. This study provides strategic insights and recommendations for stakeholders to develop and implement effective cash waqf models, enhancing the financial sustainability of Islamic educational institutions in Aceh.